Mental imagery and breathing exercises integrated into a standardized warm-up routine enhance sympathetic activation and optimize muscular performance in firefighters - Jean Philippe Biéchy; Camille Charissou; Candice Groléas; Thomas Skrysinski; Sylvain Gobert; David Amarantini; Lilian Fautrelle (PLoS ONE, 2025)
The capacity of firefighters to consistently mobilize their full physical potential during duty shifts is of paramount importance. One promising approach to achieving this goal involves developing operational protocols that effectively activate the sympathetic nervous system and vagal regulation prior to each professional action. This study investigated the effects of combining mental imagery and conscious breathing exercises with a conventional and standard warm-up on cardiac modulations, muscular strength and endurance performance in 34 firefighters randomly assigned to one of two groups: a control group (n = 17), which performed only the conventional and standard warm-up, and an experimental group (n = 17), which performed the standard warm-up in combination with mental imagery and breathing exercises. The results showed that incorporating such psychophysiological techniques into a conventional warm-up routine during repeated physical efforts optimizes sympathetic spectral power, heart rate responses, and physical performances, including maximal voluntary isometric handgrip contraction, maximum push-ups, and the maximal abdominal plank duration. Altogether, these findings indicate that brief mental imagery and controlled breathing exercises incorporated into standard warm-up routines effectively preserve muscular performance under repeated exertion while enhancing sympathetic activation, offering a practical and immediately applicable strategy to optimize firefighters’ operational readiness.